Macrophages of the cardiorenal axis and myocardial infarction - Kercheva, Maria; Ryabov, Vyacheslav; Gombozhapova, Aleksandra; Stepanov, Ivan; Kzhyshkowska, Julia (Biomedicines, 2023)
The aim of our study was to compare the features of macrophage (mf) composition of the kidneys in patients with fatal myocardial infarction (MI) and in patients without cardiovascular diseases (CVD). We used kidney fragments taken during autopsy. Macrophage infiltration was assessed by immunohistochemistry: antibodies CD68 were used as a common mf marker, CD80—M1 type mf marker, CD163, CD206, and stabilin-1—M2 type. Macrophage composition of the kidneys in patients with fatal MI was characterized by the predominance of CD163+ cells among studied cells, and the control group was characterized by the predominance of CD163+, CD206+, and CD68+. In patients with MI, biphasic response from kidney cells was characterized for CD80+ and CD206+: their number decreased by the long-term period of MI; other cells did not show any dynamics. The exact number of CD80+ cells in kidneys of individuals without CVD was slightly higher than in patients with MI, and the number of CD206+—strikingly predominant. Subsequent analysis of CD80+ and CD206+ cells in a larger sample, as well as comparison of data with results obtained from survivors of MI, may bring us closer to understanding whether the influence on these cells can serve as a new target in personalized therapy in postinfarction complications.
Gesehen am 10.09.2024